“Familias disfuncionales y sustitución de roles en los estudiantes de bachillerato de la Unidad Educativa Isabel de Godín, período abril-septiembre del 2016” - Guaranga Vega, Erika Alexandra (2017)
The present research was developed in the Isabel de Godín Educational Unit of the City of Riobamba, in the period April - September, being relevant in the psychological field. The objective is to relate the family dysfunction and role substitution of students of the Isabel de Godín Educational Unit, with a population of 218 second year high school students by selecting a sample of 60 students with dysfunctional and severely dysfunctional families, through the application of the Family functioning test FF - SIL. The research is quantitative, psychometric, non-experimental; Of transversal, documentary and field type, with a descriptive and correlational level. For the collection of data: Family Performance Test FF-SIL, with the purpose of identifying the family type, and a survey that consists of 5 items to determine the existence of role substitution. After the application of instruments and tabulation of the results it is concluded that 70% of students replace roles in their families, through the statistical analysis of Pearson's CHI square, it is established that the results of this relationship of variables such as families Dysfunctional and substitution roles are statistically significant.